Experimental investigation of the effects of social pressure and environmental uncertainty on budgetary slack. - Goh, Wan Jou. (2008)
This study extends this branch of research by using a laboratory experiment to examine the effects of environmental uncertainty and social pressure on slack creation. The laboratory experiment was a 2x2 between-subjects design, derived from crossing two independent variables: high versus low social pressure and high versus low environmental uncertainty.